The Exploration of Reading Strategies Employed by Thai EFL Students (A Case Study of Bangkok University) - Jenpattarakul, Win (Richtmann Publishing, 2012)
The purposes of this research were to 1) investigate the use of reading strategies of second-year students at BangkokUniversity 2) compare the use of reading strategies between the achievers and underachievers 3) compare the use of readingstrategies of second-year students who have different years of studying English and different reading behavior outside of class.The instruments used for collecting data were a questionnaire and an in-depth interview. Proportional stratified random samplingwas employed to formulate a sample of 370 students from nine faculties of Bangkok University. The data were statisticallyanalyzed in terms of mean and standard deviation. A t-test analysis was used to find the difference between the achievers andunderachievers on the use of reading strategies. In addition, One-way Analysis of Variance (ANOVA) was used to compare theuse of reading strategies of students with different years of studying English and different reading behavior outside of class. Forthe in-depth interview, six students with highest scores and six with the lowest scores are randomized through simple randomsampling technique to give their opinions on three questions provided, and the data were collected to assure the results of thestudy. The results of this study showed that the overall usage of reading strategies of Bangkok University students was at amedium level, and significant differences existed in reading strategies usage of three independent variables : 1) the achieversand underachiever 2) the students with different years of studying English 3) the students with different reading behavior outsideof class. The findings of this research would help the teachers to improve the process and material for teaching and learningreading strategies and raise awareness of reading strategies among the students in order to enhance the students’ readingcomprehension. Pedagogical implications into reading strategies were suggested.